2017
DOI: 10.1039/c7cp02219k
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and improving aggregated gold nanoparticle/dsDNA interactions by molecular spectroscopy and deconvolution methods

Abstract: It is well known that single-stranded DNA (ssDNA) is easily able to adsorb on citrate-capped, non-functionalized gold nanoparticles (AuNPs). However, the affinity of double-stranded DNA (dsDNA) for them is much more limited. The present work demonstrates that long dsDNA suffers from a bending conformational change when anionic nanoparticles are present in solution. A striking decrease in the persistence length of the double helix in the absence of salt is observed through dynamic light scattering (DLS), viscom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…Thus, the great decrease in the diameter corresponding to Au@16-Ph-16/DNA-5-Fu nanocomplexes, which varied from 16 to 88 nm, in comparison with the diameter of the free DNA in solution, agreed with the biopolymer compaction process induced by the precursor described in Section 3.1. Note that the great decrease in the diameter observed for the C 3 formulation in comparison with C 1 and C 2 could be attributed to the higher C DNA concentration used for the C 3 coating, which led to additional stability [64]. Thus, in accordance with absorbance experiments in Figure 4, an excess of DNA led to stable solutions, resulting in shifts in the SPR peak and significantly negative zeta potentials.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Thus, the great decrease in the diameter corresponding to Au@16-Ph-16/DNA-5-Fu nanocomplexes, which varied from 16 to 88 nm, in comparison with the diameter of the free DNA in solution, agreed with the biopolymer compaction process induced by the precursor described in Section 3.1. Note that the great decrease in the diameter observed for the C 3 formulation in comparison with C 1 and C 2 could be attributed to the higher C DNA concentration used for the C 3 coating, which led to additional stability [64]. Thus, in accordance with absorbance experiments in Figure 4, an excess of DNA led to stable solutions, resulting in shifts in the SPR peak and significantly negative zeta potentials.…”
Section: Resultssupporting
confidence: 58%
“…Moreover, through the moderate aggregation phenomena observed for Ni precursors at a low salt content, long ds-DNA polymers could protect Au@16-Ph-16 against salt-induced aggregation; this protective effect was more pronounced at higher biopolymer concentrations (formulation C 3 ). As we know, a low salt addition to DNA can cause conformational changes in the biomolecule and can also alter its interaction with gold nanoparticles [56,57,64]. The observed behavior is compatible with the DNA shrinkage induced at low salt content that contributes to nanoparticle stabilization [64].…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…An isosbestic point also appears over 258 nm, as has been previously observed for anionic nanoparticles and large DNA chains. 53 This small conformational change does not involve an opening of the double helix due to the nanoparticles; the negative band does not decrease in intensity, which would correspond to a loss of helicity of the DNA, and the crossover point does not change, while Dias and coworkers found that for melting processes, a 3 nm shi could be expected. 54 Even at 70 C, the essential feature characteristic to the B-form remains (see Fig.…”
Section: Resultsmentioning
confidence: 95%
“…5,51,52 It has also be considered that at room temperature the AuNPs and DNA molecules are inclined to be distant (due to they present the same charge) and therefore the binding is rather difficult. 24,53 As the temperature increases the thermal uctuation too, so that the chances to collide of the AuNPs with DNA molecules are higher, being possible surpassing the energy barrier which avoids their approximation. In addition the partial denaturation of DNA can happen at higher temperatures, so the exposition of DNA's bases to the outside is viable and the interaction between bases and AuNPs does not need to overlap the repulsion electrostatic energy.…”
Section: Resultsmentioning
confidence: 99%